Poverty and the law - Robson, Peter, 1947-; Kjønstad, Asbjørn (Oñati international series in law and society., 2001)
This collection of essays focuses attention on the global impact of legal policies on levels of poverty. They illustrate the distinct dimensions of poverty in a range of different political and cultural settings and also show how poverty is exacerbated by quite discrete local cultural factors in some instances. There is, nonetheless a universal element which runs through all the contributions. The fate of those who are disadvantaged in society depends crucially on their access to goods through the world of work. Thus gender, ethnic background or disability can result in individuals having a muc.